UPACARA KEMATIAN SAUR MATUA BATAK TOBA: ANALISIS TRADISI LISAN - Relly Monika Hasugian (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
This study reports funeral ceremony tradition of Saur Matua of Batak Toba, Indonesia.  Oral tradition is the traditional delivered orally using words, transformed by the times and the adjustment to the context of the times.  A qualitative using ethnograpic approach is used in this study.  Data were explored from an observation and an in-depth interview on the conduct of Saur Matua ceremony.  The study revealed that Saur Matua in Toba Batak has 10 full characteristics  of oral tradition: (1) Representing the events as the context; (2) Having a cultural activity; (3) To be observed and watched; (4) Traditional characteristics; (5) Inherited from generation to generation; (6) Delivering process "from mouth to ear"; (7) Containing the values and cultural norms; (8) Having variety version; (9) Owned jointly by a particular community, and (10) Potentially revitalized and raised as a source of cultural industries. The Saur Matua has a text, co-text, context, value or norm, meaning or function and local wisdom that must be preserved continuously by generations to be not lost from the death tradition in Toba Batak society.